Categorical-functorial analysis of bakery production - Kyshenko, Vasil; Pankov, Dmitry (My University, 2017)
Knowledge characterization issues based on mathematical theory of categories and functors are studied. Categorical-functorial analysis of bakery production functioning as intelligent control object is conducted. The categories analysis results that characterize the quality of raw materials, part finished and finished bakery production items are presented. The conclusions below about the prospects of this approach implementation are shown. Розглянуті питання формалізації знань на основі математичної теорії категорій та функторів. Проведений категорійно-функторний аналіз функціонування хлібопекарського виробництва як об’єкта інтелектуального керування. Наведено результати аналізу категорій, що характеризують якість сировини, напівфабрикатів та готової продукції хлібопекарського виробництва. Наведені висновки про перспективність використання даного підходу.
Categorical-functorial analysis of bakery production
Keywords: хлібопекарське виробництво; bakery production; якість продукції; products quality; категорійно-функторний аналіз; categorical-functorial analysis; інтелектуальне керування; intelligent control; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка